Content Analysis and Social Construction of Power and Resistance in Dressrosa Arc of One Piece Anime: A Foucauldian Perspective - Muhammad Zufarrafif Faizaristo; Alfian Muhazir, M.A (Jogjakarta Communication Conference (JCC), 2026)
This study examines the construction of power and resistance in the Dressrosa Arc of the One Piece anime through qualitative content analysis and social construction theory. Popular media functions as an arena where social meanings are shaped, given meaning, and widely distributed through narratives, symbols, and visual representations. Using Michel Foucault's power theory framework, this research analyzes how power is represented through discourse, normalization, and knowledge-power relations in the Dressrosa Arc. The research method employs qualitative content analysis on 118 episodes (629-746) with systematic coding procedures based on Foucault's theoretical framework. The findings reveal that power in Dressrosa is constructed through five main categories: power discourse (WK), truth production (PK), normalization of domination (ND), knowledge-power relations (RPK), and resistance practices (PR). Visual symbols and narrative structures play a crucial role in legitimizing authoritarian power through manipulation of information, memory control, and systematic violence. The analysis demonstrates that resistance emerges through solidarity, collective action, and counter-narratives that challenge dominant power structures. This study contributes to communication science by demonstrating how popular media constructs power meanings through audiovisual texts and how audiences interpret power dynamics and resistance symbolically. The findings provide insights into media literacy, critical analysis of popular culture, and understanding of contemporary power relations.